Protecting buyers from fine print - D'Agostino, Elena; Seidmann, Daniel J. (Elsevier, 2016)
Buyers typically do not read the …ne print in contracts, providing an incentive for a monopolist to draft terms which are unfavorable to buyers. We model this problem, proving that trade must then be inefficient. We show that regulation which mandates efficient terms raises welfare. More interestingly, regulations which prohibit the least efficient terms may reduce welfare by inducing the monopolist not to other favorable terms. We extend these results to markets in which some buyers are naive, showing that prohibiting the least efficient terms may also harm the naive buyers.